Production of Oleic Acid Ethyl Ester Catalyzed by Crude Rice Bran (Oryza sativa) Lipase in a Modified Fed-batch System: A Problem and its Solution - Pudji Hastuti; Indro Prastowo; Chusnul Hidayat (Bulletin of Chemical Reaction Engineering & Catalysis, 2015)
A fed-batch system was modified for the enzymatic production of Oleic Acid Ethyl Ester (OAEE) using rice bran (Oryza sativa) lipase by retaining the substrate molar ratio (ethanol/oleic acid) at 2.05:1 during the reaction. It resulted in an increase in the ester conversion of up to 76.8% in the first 6 h of the reaction, which was then followed by a decrease from 76.8% to 22.9% in 6 h later. The production of water in the reaction system also showed a similar trend. The water was hypothesized to lead lipase to reverse the reaction which resulted in a decrease in both (water and esters) in the last 6 h of the reac- tion. In order to overcome the problem, zeolite powder (25 and 50 mg/mL) were added into the reaction system at 5 h of the reaction. As the result, the final ester conversions increased drastically up to 90 - 95.7%. Thus, the combination of a constant substrate molar ratio (ethanol/oleic acid) during the reaction (at 2.05:1) with the addition of zeolite powder (25 and 50 mg/mL) to the reaction system at 5 h is effective for the enzymatic synthesis of OAEE. Copyright © 2015 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).